Sifat Fisikokimia dan Organoleptik Bolu Gulung Gluten Free Berbahan Tepung Ketan Hitam (Oryza sativa L. var. glutinosa) dan Tepung Maizena (Amylum maydis) - Michelle; Fadjar Kurnia Hartati; Retnani Rahmiati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to examine the effect of black glutinous rice flour and cornstarch on the physicochemical and organoleptic properties of gluten-free sponge rolls, and find the best combination of the two ingredients. This study was conducted using a Complete Random Design (RAL) which has one factor and consists of four treatments. The treatment consisted of varying the proportion of black glutinous rice flour (H) and cornstarch (M) with the same total amount of flour (60 g) in each treatment, namely H1:M1 (60g:0g), H2:M2 (54g:6g), H3:M3 (48g:12g), and H4:M4 (42g:18g) which were repeated three times each. The results of the study show that for the manufacture of gluten-free sponge rolls, the H4M4 treatment is recommended as the best formulation because it provides the most optimal results compared to other treatments. Statistically, the H4M4 treatment showed a marked difference in some of the parameters tested (p<0.05). The formulation in the H4M4 treatment contains a crude fiber content of 2%, a moisture content of 50.91%, a development capacity of 66.19%, and a stability of 100%. The results of the likability level test showed a taste value of 4.30 (likes), aroma 4.17 (likes), color 4.25 (likes), and softness of 4.45 (likes), and produced the highest effectiveness value of 0.82.